The complete mitochondrial genome of the extinct Pleistocene horse (Equus cf. lenensis) from Kotelny Island (New Siberian Islands, Russia) and its phylogenetic assessment. Issue 1 (2nd January 2020) - Nedoluzhko, Artem V.; Sharko, Fedor S.; Boulygina, Eugenia S.; Tsygankova, Svetlana V.; Slobodova, Natalia V.; Gruzdeva, Natalia M.; Rastorguev, Sergey M.; Spasskaya, Natalia N.; Maschenko, Evgeny N.
Abstract: The complete mitochondrial genome from the Pleistocene stallion horse ( Equus cf. lenensis ) which complete skull was found in 1901 on Kotelny Island (New Siberian Archipelago, Sakha Republic, Russia) is published in this paper. The mitochondrial DNA (mtDNA) is 16, 584 base pairs (bp) in length and contained 13 protein-coding genes, 2 rRNA genes, 22 tRNA genes. The overall base composition of the genome in descending order was 32.3% – A, 28.5% – C, 13.4% – G, 25.8% - T without a significant AT bias of 58.2%.